Hinges (2015), book three ebook Mechanical men. - McClaren, Meredith (Hinges (2015)., 2018)
Adrift without Bauble, Orio returns to the only comfort she has left in the city of Cobble. But dark days have visited the city in her absence. And the mechanizations of single-minded men will threaten them further unless Orio can find it within herself to stop it. HINGES, BOOK 3: MECHANICAL MEN will conclude this fantasy webcomic series.. Author: Meredith Mcclaren. Illustrator: Meredith Mcclaren [Author]. 2017 Meredith McClaren..